Metal-free approach towards efficient synthesis of FDCA using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst and oxone over two steps from HMF, fructose and glucose - Tamboli, Asma T. Biradar; Kirdant, Swapnali P.; Jadhav, Vrushali H. (New Journal of Chemistry, 2022)
In this work, a metal-free approach towards the synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF), fructose and glucose is reported over two steps using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst (p-TSA-POM) in the first step and oxone as an oxidant in the second step. HMF, fructose and glucose were converted to 2,5-diformylfuran (DFF) using the p-TSA-POM catalyst followed by oxidation of DFF to FDCA using oxone. To the best of our knowledge, this is the first metal-free approach for the synthesis of FDCA directly from glucose. DFF was obtained from HMF in 91% yield, whereas it was obtained in 85% and 61% yields from fructose & glucose, respectively. DFF was further converted to FDCA using oxone as an oxidant. FDCA was obtained in an overall yield of 84%, 78% and 56% from HMF, fructose & glucose, respectively.